Folktales for Environmental Conservation: From Oral Traditions to Ecological Wisdom - Abubakari, Hasiyatu (African studies (Johannesburg), 2025)
The oral tradition of any given community provides a rich source of information on its history, culture and indigenous knowledge that guide the people on local approaches towards handling various situations that may or may not be detrimental to human survival. This study explores the role of folktales in advancing environmental conservation among the Kusaas of Ghana. Using frameworks such as literary anthropology and environmental ethics, it demonstrates how these oral literary narratives convey indigenous approaches to environmental education paying particular attention to biodiversity preservation and ecological balance. Employing qualitative methods, the study investigates folktales that were collected from six Kusaal-speaking districts in Ghana, exhibiting their potentials as tools for cultural education, eco-consciousness, and environmental activism. The stories mirror a blend of anthropocentrism, biocentrism and theocentrism, offering invaluable insights for community-based climate resilience strategies in Ghana and beyond. The research emphasises the relevance of decolonial approaches to environmental education that engage grassroots communities through culturally relevant mediums.